Melt linear viscoelastic rheological analysis to assess the microstructure of polyamide 6–acrylonitrile butadiene styrene terpolymer immiscible blends via the application of fractional Zener and Coran models. Issue 42 (11th July 2017) - Aminjafari, Mahboobeh; Entezam, Mehdi; Sadeghi, Morteza; Masoumi, Mahmood; Khonakdar, Hossein Ali; Jafari, Seyed Hassan
ABSTRACT: In this study, the melt linear viscoelastic rheological properties of polyamide 6 (PA6)–acrylonitrile butadiene styrene terpolymer (ABS) immiscible blends were analyzed with the help of Coran and fractional Zener models (FZMs) to assess the microstructure of the blends. For this purpose, dynamic shear flow experiments and scanning electron microscopy investigations were performed. The nonzero value of the elastic modulus of the spring element ( G e ) of the FZM for ABS‐rich blends was explained by the formation of a networklike structure because of the agglomeration of the rubber phases of the ABS matrix, whereas for the PA6‐rich blends with a high content of ABS, the interactions and/or interconnectivity of the ABS dispersed phase led to a nonzero value of Ge . The value of the fitting parameter of the Coran model ( f ) was near to 0.5 for the 50/50 blend; this was fully in agreement with the formed cocontinuous morphology for this blend composition. On the other hand, the f value for the blends with a matrix–droplet‐type morphology was near to zero for the PA6‐rich blends; this indicated the lower continuity of the ABS dispersed phase as a harder phase compared to the PA6 soft matrix, whereas the f value was near to 1 for ABS‐rich blends. This confirmed the formation of an interconnected networklike structure for this series of blends. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2017, 134, 45423. Abstract :